FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN NON KEUANGAN DI INDONESIA - MARIA, MARIA; ERINA, CLARA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study is to analyze and obtain an empirical evidence about the influence of independent variables on firm value. These independent variables are profitability, leverage, liquidity, firm size, dividend policy, company growth, managerial ownership, institutional ownership, board of independent commissioners, and audit committee. The population used in this research are non financial companies listed in Indonesian Stock Exchange during period 2015-2019. The method used in sample selection in this study is purposive sampling method and there are 44 companies selected as final samples. In this study, the hypothesis is tested by using multiple regression analysis. The result of this research shows that profitability, leverage, company growth, and board of independent commissioners have influence on firm value, while liquidity, firm size, dividend policy, managerial ownership, institutional ownership, and audit committee have no influence on firm value